Towards the Implementation of an Intelligent ERP System: Guidelines for Building Intelligent ERP Systems - Sousa, Filipe Inácio Ferreira da Silva de (2022)
Dissertation presented as the partial requirement for obtaining a Master's degree in Information Management, specialization in Information Systems and Technologies Management